Statement of the Problem of Determining the Technical Appearance and Design Characteristics of Multi-Apartment Residential Buildings Based on the Expert Systems Method - Alexander A. Merkulov; Yury N. Razoumny; Olga A. Saltykova; Ivan V. Stepanyan (RUDN Journal of Engineering Research)
The article discusses various methods for creating decision support systems to determine the technical appearance and design characteristics of multi-apartment residential buildings at the pre-construction stage. To solve this problem, structural optimization is used, which includes determining the number of elevators, the height of the building and the number of floors, orienting the building to the cardinal directions, determining the parameters of engineering communications and the investment attractiveness of new housing. The advantages and disadvantages of machine learning methods and various types of logical inference in expert systems for determining the technical appearance and design characteristics of multiapartment residential buildings are analyzed. A comparative analysis of the various approaches has led to the conclusion that the tools of expert systems based on fuzzy logic are the most advisable. This paper presents an overview of the fundamental principles underlying the operation of fuzzy expert systems. It also offers a critical assessment of their potential for universal applicability and versatility in addressing design challenges related to construction projects.